CHALLENGES AND STRATEGIES FOR MANAGING GERD DISEASE IN ADOLESCENTS - Ahmadi, Dela Andika; Susanti, Nofi; Refiana, Revail; Annisa, Rifa (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
Gastroesophageal Reflux Disease (GERD) is a health problem that is increasing in prevalence throughout the world. The aim of this research is to evaluate the challenges and strategies for managing GERD through a literature study. This research method involves searching and analyzing various sources of information relevant to the topic of GERD disease management. Selection of information sources is carried out based on predetermined inclusion and exclusion criteria, including relevance to the topic, year of publication, and methodological quality. This research is a type of qualitative research in the nature of a literature study (Library Search) which uses literature as the main research object. Data obtained from literature studies were then analyzed systematically to identify patterns, trends and main findings related to challenges and strategies for managing GERD. The research results show that the main challenges in managing GERD include the diversity of symptoms, risk factors such as unhealthy eating patterns and smoking habits, as well as the side effects of long-term medical treatment. Effective management strategies include a combination of medical treatment with healthy lifestyle changes and cognitive behavioral therapy. This holistic approach not only helps reduce GERD symptoms, but also prevents long-term complications such as esophagitis and esophageal cancer. By paying attention to the challenges faced and implementing appropriate management strategies, it is hoped that we can improve the quality of life of GERD patients and reduce the overall disease burden on the health system. This research provides a better understanding of the management of GERD and provides a basis for the development of more optimal approaches to managing this disease.